A Bibliometric and Systematic Literature Review on the Concept, Dimensions, and Measurement of Sustainable Financial Literacy - Vikneswary Tirumalaisamy; Noraini binti Moktar; Rakhmawati, Antin (SKeTsa Bisnis (e-jurnal), 2025)
Introduction; Sustainable Financial Literacy (SFL) is a key 21st-century competency that integrates traditional financial literacy with awareness of environmental, social, and governance (ESG) aspects in economic decision-making. As sustainability challenges become increasingly central to global economic systems, understanding SFL has become essential for promoting responsible and ethical financial behavior. Method;This study employs a bibliometric and systematic literature review (SLR) approach on 357 relevant scholarly articles to map the evolution of the concept, publication trends, and measurement instruments of SFL. The bibliometric analysis was conducted to identify patterns of author collaboration, contributing countries, and dominant research domains. Meanwhile, the systematic analysis examined the conceptual and empirical dimensions of SFL, encompassing the cognitive (knowledge), affective (attitudes and values), and behavioral (sustainable financial actions) domains. Results; The findings indicate that SFL remains a relatively new research field, with major attention directed toward the integration of ESG principles into financial education, green investment, and digital financial inclusion. The measurement of SFL varies across studies, ranging from ordinal to ratio scales, and typically assesses knowledge, attitudes, and behaviors in a quantifiable manner. Conclusion; These findings underscore the strategic role of Sustainable Financial Literacy in enhancing sustainable investment decisions, fostering ethical financial behavior, and serving as a critical foundation in supporting the transition toward a green, inclusive, and ethical economy.